Can Melissa officinalis improve chromatin structure and sperm parameters in a rat model of varicocele?. (6th June 2018) - Rezakhaniha, Bijan; Heidari, Reza; Abbasi, Mehdi
Abstract: Excessive production of reactive oxygen species is a central mechanism in the pathology of varicocele; Melissa officinalis (MO) is a medicinal plant from the Lamiaceae family that has antioxidant activity. In this study, we have investigated the potential therapeutic effect of MO on sperm parameters and chromatin structure in varicocelised rat. Male Wistar rats were randomly assigned to control, sham, varicocele, MO treatment and placebo groups. Rats in varicocele, MO treatment and placebo groups underwent left varicocele induction. Following the operation, rats in placebo and MO treatment groups received normal saline or MO extract, daily for 10 weeks respectively. At 10 weeks after varicocele induction, sperm chromatin and parameters were evaluated in all groups. Chromatin structure was evaluated by aniline blue, acridine orange and toluidine blue staining. All three staining outcomes were increased in varicocele and placebo compared control (and sham) groups ( p  < 0.05). Sperm count, motility, morphology and vitality were decreased between varicocele and control (and sham) group ( p  < 0.05). Sperm parameters and chromatin staining (else AB staining) outcomes improve in MO treatment compared to varicocele and placebo groups ( p  < 0.05). These findings suggest that MO ameliorate the harmful effect of varicocele on sperm parameters and chromatin structure.